An advanced iterative model for computing approximated blocking probabilities and measuring the quality of service in optical communication networks. Issue 5 (1st February 2021) - Khan, Akhtar Nawaz; Ali, Amjad; Imtiaz, Waqas A.; Ullah, Sibghat
Abstract: Existing analytical models (EAMs) are used to find the quality of service of optical networks with wavelength division multiplexing (WDM). However, the convergence of EAMs decreases with an increase in traffic load and the numbers of wavelength (w) channels. EAMs are used to compute approximated numerical values of blocking probabilities (BPs) which are based on an iterative approach. There are cases in EAMs when numerical BP values do not converge to a single point after numerous iterations. In this paper, the converge issues of EAMs have been addressed by considering a recursive approximation based on iterative approach with the convergence criteria which is called an advance approximated BP model (AABPM). The accuracy of the AABPM for WDM optical networks is examined by comparing with an EAM as well as simulation results which shows that AABPM converges to give similar approximated numerical values with less convergence time.